2005
DOI: 10.1016/j.febslet.2005.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of temperature induced conformation change with optimum catalytic activity in the recombinant G/11 xylanase A fromBacillus subtilisstrain 168 (1A1)

Abstract: The 1.7 Å resolution crystal structure of recombinant family G/11 b-1,4-xylanase (rXynA) from Bacillus subtilis 1A1 shows a jellyroll fold in which two curved b-sheets form the active-site and substrate-binding cleft. The onset of thermal denaturation of rXynA occurs at 328 K, in excellent agreement with the optimum catalytic temperature. Molecular dynamics simulations at temperatures of 298-328 K demonstrate that below the optimum temperature the thumb loop and palm domain adopt a closed conformation. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 39 publications
3
43
0
2
Order By: Relevance
“…A fingers region and a palm region comprised of β-sheet structures form the floor and a wall of the active site cleft, respectively. The thumb region is comprised of a short two stranded β-sheet, which forms the opposing wall of the active site cleft, and has been shown to be highly flexible [1][2][3][7][8][9]. Recently the role of conformational flexibility of the thumb loops of family GH11 xylanases has been the focus of debate in the literature [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A fingers region and a palm region comprised of β-sheet structures form the floor and a wall of the active site cleft, respectively. The thumb region is comprised of a short two stranded β-sheet, which forms the opposing wall of the active site cleft, and has been shown to be highly flexible [1][2][3][7][8][9]. Recently the role of conformational flexibility of the thumb loops of family GH11 xylanases has been the focus of debate in the literature [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The thumb region is comprised of a short two stranded β-sheet, which forms the opposing wall of the active site cleft, and has been shown to be highly flexible [1][2][3][7][8][9]. Recently the role of conformational flexibility of the thumb loops of family GH11 xylanases has been the focus of debate in the literature [2][3][4][5][6][7]. The primary structure of the thumb region is highly conserved throughout the family GH11 xylanases, and comparative studies of the crystal structures and molecular dynamics (MD) simulations have suggested that the thumb sequence is the most flexible region in the molecule [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylanases (endo-1,4-␤-xylanase, EC 3.2.1.8) are important enzymes for hemicellulose degradation, hydrolyzing the ␤-1,4-glycosidic bonds between xylose residues in xylan (12); family 11 xylanases display a jelly roll fold including a single ␣-helix and two twisted ␤-sheets (13,14). In common with all GH11 xylanases, the structure of B. subtilis xylanase A (XynA) resembles a right hand, where the ␤-strands form the finger and palm domains that constitute the active site cleft, access to which is regulated by movements of a flexible ␤-turn structure denominated as the "thumb" domain (15,16).…”
mentioning
confidence: 99%
“…Although, details of peptide insertion and positioning in the membranes are of particular interest so that more realistic models concerning the action of AMPs can be achieved, knowledge about models of interactions between AMPs and membranes is still subject to the limited information obtained from experiments. In this sense, computational techniques have been used to solve many problems concerning biological systems and to complement experimental observations (Murakami et al, 2005;Brancaleoni et al, 2006;Mazzé et al, 2007;Fuzo et al, 2008). Among the various computational techniques, molecular dynamics simulation (Alder and Wainwright, 1957) is a powerful tool that provides detailed configurational and dynamic information at the atomic level.…”
Section: Introductionmentioning
confidence: 99%